A method for regional-scale assessment of vegetation recovery time after high-severity wildfires: Case study of Spain. (October 2014) - Rodrigues, Marcos; Ibarra, Paloma; Echeverría, Maite; Pérez-Cabello, Fernando; Riva, Juan de la
This study aims to develop a method to estimate the recovery time of plant communities after high-severity wildfires. The designed methodology is based on map algebra and a geographical information system, which enabled calculation of the approximate time required to restore vegetation to conditions similar to pre-fire regarding plant height and canopy cover. The methodology considered, first, the vegetation in the territory, characterized by the structure of the dominant plant community (tree, shrub, or grassland) and its regeneration strategy (resprouter or seeder); and, second, two of the main factors determining recovery time – water availability and soil loss. We also considered the influence of observed rainfall trends over the past 50 years on these latter two factors. The methodology was applied to Spain to test its performance. The results suggest a period of 2 and approximately 100 years for grassland communities and tree communities with low germination, respectively. There are significant differences in plant communities between the two biogeographic regions (Euro-Siberian and Mediterranean) as well as within each community, directly linked to variability in terrain and climatic conditions.